Epigenetic Features of Human Perinatal Stem Cells Redefine Their Stemness Potential - Giulia Gaggi (Cells, 2020)
Human perinatal stem cells (SCs) can be isolated from fetal annexes without ethical or safety limitations. They are generally considered multipotent; nevertheless, their biological characteristics are still not fully understood. The aim of this study was to investigate the pluripotency potential of human perinatal SCs as compared to human induced pluripotent stem cells (hiPSCs). Despite the low expression of the pluripotent factors NANOG, OCT4, SOX2, and C-KIT in perinatal SC, we observed minor differences in the promoters DNA-methylation profile of these genes with respect to hiPSCs; we also demonstrated that in perinatal SCs miR-145-5p had an inverse trend in comparison to these stemness markers, suggesting that NANOG, OCT4, and SOX2 were regulated at the post-transcriptional level. The reduced expression of stemness markers was also associated with shorter telomere lengths and shift of the oxidative metabolism between hiPSCs and fetal annex-derived cells. Our findings indicate the differentiation ability of perinatal SCs might not be restricted to the mesenchymal lineage due to an epigenetic barrier, but other regulatory mechanisms such as telomere shortening or metabolic changes might impair their differentiation potential and challenge their clinical application.